Evidence of Both Surface and Bulk Dirac Bands and Anisotropic Nonsaturating Magnetoresistance in ZrSiS. (1st August 2016) - Wang, Xuefeng; Pan, Xingchen; Gao, Ming; Yu, Jihai; Jiang, Juan; Zhang, Junran; Zuo, Huakun; Zhang, Minhao; Wei, Zhongxia; Niu, Wei; Xia, Zhengcai; Wan, Xiangang; et al.
Abstract : ZrSiS materials show unsaturated magnetoresistance until a magnetic field of 53 T with a butterfly‐shaped angular dependence. Intense Shubnikov‐de Haas oscillations resolve a bulk Dirac cone with a nontrivial Berry phase. Combined with angle‐resolved photoemission spectroscopy and theoretical calculations, ZrSiS is proved to be a Dirac material with both surface and bulk Dirac bands.